2018
DOI: 10.1017/jfm.2018.356
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the flame–wall interaction in premixed turbulent combustion

Abstract: The present work focuses on the flame–wall interaction (FWI) based on direct numerical simulations (DNS) of a head-on premixed flame quenching configuration at the statistically stationary state. The effects of FWI on the turbulent flame temperature, wall heat flux, flame dynamics and flow structures were investigated. In turbulent head-on quenching, particularly for high turbulence intensity, the distorted flames generally consist of the head-on flame part and the entrained flame part. The flame properties ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 57 publications
1
22
0
1
Order By: Relevance
“…More recently, FWI has been investigated in turbulent channel flow using DNS by Gruber et al (2010) in the case of a V-flame, and by Gruber et al (2012Gruber et al ( , 2018, Kitano et al (2015) and Ahmed et al (2019) in the case of turbulent boundary layer flashback. Statistically planar turbulent premixed flames impinging on a flat inert wall at different temperatures have been investigated by Zhao et al (2018aZhao et al ( , b, 2019. These studies have shown that the flame front has a strong influence on the approaching turbulence and at the same time the turbulence significantly affects the flame structure.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, FWI has been investigated in turbulent channel flow using DNS by Gruber et al (2010) in the case of a V-flame, and by Gruber et al (2012Gruber et al ( , 2018, Kitano et al (2015) and Ahmed et al (2019) in the case of turbulent boundary layer flashback. Statistically planar turbulent premixed flames impinging on a flat inert wall at different temperatures have been investigated by Zhao et al (2018aZhao et al ( , b, 2019. These studies have shown that the flame front has a strong influence on the approaching turbulence and at the same time the turbulence significantly affects the flame structure.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, quenching occurs only in the near-wall part of the flame. A recently proposed stationary FWI configuration shows advantages in various aspects in understanding FWI [9]. In this type of FWI, the heat loss is directed from the flame zone to the burnt mixture, unlike the situation in the HOQ and SWQ configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on premixed flames for spark-ignition (SI) engines show the main features of transient heat flux curves. 6,7,21,22 The heat flux first increases in a fraction of millisecond from zero to a few MW/m 2 and decreases in about the same time. That heat flux spike is attributed to flame wall interaction (FWI) processes: the hot flame front, close to the adiabatic flame temperature, approaches the wall until heat losses cause flame quenching.…”
Section: Introductionmentioning
confidence: 99%